IMPLEMENTASI PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM ALOKASI DANA DESA DI KAMPUNG MORUKU DISTRIK DEKAI KABUPATEN YAHUKIMO - Pahabol, Nappi; Ohoiwutun, Yosephina; Muhdiarta, Untung (Universitas Cenderawasih, 2025)
This research analyzes the implementation of community empowerment through the Village Fund Allocation Program (ADD) in Moruku Village, Dekai District, Yahukimo Regency. This research aims to understand the effectiveness of ADD implementation and identify supporting and inhibiting factors in the process. The urgency of this research lies in the importance of optimizing ADD management to realize inclusive and sustainable village development. The approach used is a qualitative method with data collection techniques in the form of in-depth interviews, participatory observation, and documentation. Informants were determined using purposive sampling technique, involving village officials, communities, and related stakeholders. Data were analyzed using the Miles and Huberman interactive model. The results showed that the implementation of ADD in Moruku Village was not optimal due to low community participation and the dominance of the village head in managing funds. Based on Edwards III's policy implementation theory, analysis of communication, resources, disposition, and bureaucratic structure reveals that communication is still limited, human resources and infrastructure are inadequate, and bureaucratic mechanisms are less effective in ensuring transparency and accountability. The main supporting factors are the availability of routinely allocated funds and the potential of local natural resources, while inhibiting factors include the weak capacity of village officials, lack of supervision, and low community literacy regarding fund management. This research emphasizes the need for improved communication between village governments and communities, strengthened human resource capacity, and structural reforms in ADD governance to make it more transparent and participatory. The main recommendation is to improve external and internal supervision and active involvement of the community in every stage of program implementation.